2017
DOI: 10.3390/sym9030032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cyber Security and Modelling of Risk Propagation with Petri Nets

Abstract: This article presents a new method of risk propagation among associated elements. On the basis of coloured Petri nets, a new class called propagation nets is defined. This class provides a formal model of a risk propagation. The proposed method allows for model relations between nodes forming the network structure. Additionally, it takes into account the bidirectional relations between components as well as relations between isomorphic, symmetrical components in various branches of the network. This method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In references 13,14, it was presented how formal methods, that is, colored Petri nets, can be used to model protocol specifications, and how formal verification can help to analyze protocol properties. In reference 15, it was presented a Petri net model that can be adapted to the propagation model of any systems' characteristics. In this study, they showed the formal model of risk propagation.…”
Section: Related Workmentioning
confidence: 99%
“…In references 13,14, it was presented how formal methods, that is, colored Petri nets, can be used to model protocol specifications, and how formal verification can help to analyze protocol properties. In reference 15, it was presented a Petri net model that can be adapted to the propagation model of any systems' characteristics. In this study, they showed the formal model of risk propagation.…”
Section: Related Workmentioning
confidence: 99%
“…These works do not cover incident propagation to connected infrastructure elements. The work of [67] addresses the impact propagation of cyber incidents using the Petri Nets model, to identify impacted elements and assess their impacts. In recent work, one of the only papers dealing with the propagation of incidents in an integrated cyber-physical context is that of [3].…”
Section: B Incident Propagation Models and Approachesmentioning
confidence: 99%
“…Its advantage is that it has strict mathematical expressions and intuitive graphical expressions. Therefore, Petri nets can also be used for network security evaluation modeling [23]. In addition, fuzzy theory is often used to resolve the uncertainty of trust relationships.…”
Section: Fuzzy Petri Netmentioning
confidence: 99%